Leiomyosarcoma: Lung Metastasis - Makhoul, Karim; Miller, Daniel; Ilyas, Usman; Hosna, Asma; Baig, Muhammad A (Curēus (Palo Alto, CA), 2023)
Uterine leiomyosarcoma distant metastasis is common, and lung metastasis has been reported. However, unique cases have been identified either with late onset of metastatic disease or with large size of lung metastasis. A typical approach to avoid metastasis would be a hysterectomy. Nonetheless, metastatic recurrence is common. We encountered a case at our hospital with leiomyosarcoma metastatic to the lungs. Lung metastasis was noted to be 17 cm in diameter. This size has not yet been reported in the literature to the best of our knowledge.